THE VOTERS’ LOYALTY DECREASING AND POLITICAL MARKETING - Полторак, В.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
Sharp change of the political parties’ orientation on the methods and technologies of cooperation with the population in the conditions of voters’ loyalty decreasing is analyzed in the article. The problems of voters’ loyalty decreasing factors, the factors of the political consumerism increasing by voters in modern Ukraine are considered in the article. The necessity of political marketing using for regulating political processes in such conditions, which allows to organize the influence on the voters’ behavior with the help of demand on the market of political products and its satisfaction considering is shown in the article.